2,4-Dihydroxy-N′-(2-hydroxy-4-methoxybenzylidene)benzohydrazide - Han, You-Yue (International Union of Crystallography, 2010)
In the title compound, C(15)H(14)N(2)O(5), the dihedral angle between the two benzene rings is 4.3 (3)° and the molecule adopts an E configuration with respect to the C=N bond. Intramolecular O—H⋯N and N—H⋯O hydrogen bonds are observed. In the crystal structure, the molecules are linked through intermolecular N—H⋯O and O—H⋯O hydrogen bonds to form layers parallel to the ac plane.